Determination of Psychological Welfare (Well-Being) at Retirement Age : A Literature Review - Clara Bonita Dinar Ristanti; Augustina Sulastri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Retirement is a phase which has to be faced by a worker in the completion of his work duties. The preparation of the process draws attention to the people who experience it or the stakeholders to provide policies on the retirement matters. This research aims to provide information about the factors which influence the welfare of life (wellbeing) in retirement. The current study used a literature review that involved nine journals that studied retirement. This research was conducted by searching for articles using an application called Publish Perish by using two keywords “Retreatment” and “Pension”. The crossref (cross reference) search found that there are 5 journals from the keyword “Pension” and 10 journals from the keyword “retreatment”. After the exclusion, nine journals were obtained according to the researcher’s desire. The result of this research shows the factors affecting the retirement’s wellbeing which are categorized by: psychology, economics, social, gender and health. Psychology deals with loneliness, anxiety, or negative psychological factors. Economics deals with income and financial support in retirement. Social problems are more related to relationships in the family and the people around them who support retirement. The health factor is always presented in every retirement situation because health becomes a big expense in retirement.